PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP KEPUASAN KONSUMEN PADA PT BERKAH SYAHRIE SEJAHTERA TANGERANG - Retno Wulansari; Kenny Astria; Wahyu Andri Wibowo (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2023)
Providing satisfaction to consumers is a strategic step in achieving company goals. Because of this, it can influence consumers to continue using the products/services being sold, so that sales volume increases and provides big profits to the company. The purpose of this study was to determine the effect of service quality and price on customer satisfaction at PT Berkah Syahrie Sejahtera Tangerang either partially or simultaneously. The method used is quantitative associative method. The sampling technique used the slovin formula and the sample in this study was 87 respondents. Data analysis used validity test, reliability test, classical assumption test, regression analysis, correlation coefficient analysis, coefficient of determination analysis and hypothesis testing. The results of this study indicate that the relationship between satisfaction with service quality and price is very large. This indicates that consumers are satisfied if they get good service and get the right price. In addition, if the company provides good prices and services simultaneously to consumers, it is possible to strengthen satisfaction which has implications for the birth of purchase loyalty